Microbial contamination of hands with or without the use of bidet toilets (electric toilet seats with water spray) after defecation. (28th December 2021) - Oie, Shigeharu; Kawai, Shinya
Abstract: Bidet toilets (electric toilet seats with water spray) are increasing in popularity worldwide. However, the extent of reduction of microbial contamination of the hands with the use of bidet toilets after defecation is unclear. Microbe contamination of the hands with and without the use of bidet toilets after defecation was examined in 32 nursing students. Double gloves were worn on the dominant hand and four layers of toilet paper were used to wipe the buttocks after defecation, and microbe contamination of the second glove (outer glove) of the double gloves was examined. The volunteers were free to select the flow volume, wash time of the bidet, and the type of bidet. Without the use of a bidet toilet, the average value ± standard deviation of the number of microbes attached to the gloves was 39, 499.3 ± 77, 768.3 colony forming units (cfu)/glove; however, it was 4, 146.9 ± 11, 427.7 cfu/glove when the bidet toilet was used. The number of microbes adhering to gloves was significantly reduced when a bidet toilet was used ( p < 0.00001, Wilcoxon signed-rank test). HIGHLIGHT: Using the bidet function of toilet is efficacious in maintaining hand hygiene. Use of bidet decreases transmission of fecal microbe to the hand.